The method of Dirichlet generating series in the theory of distribution of additive arithmetic functions. I - Kubilius, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Кубилюс. Метод производящих рядов Дирихле в теории распределения аддитивных арифметических функций. I J. Kubilius. Generuojančių Dirichlė eilučių metodas adityvinių aritmetinių funkcijų pasiskirstymo teorijose. I